Hypoglycemic Agents: Micro-Determination by Highly Sensitive and Validated Spectrophotometric Techniques. Issue 2 (4th March 2018) - Deepakumari, H.N.; Shyla, B.; Revanasiddappa, H.D.
Abstract: The objectives of our present study is to analyse the hypoglycemic agents, Linagliptin (LNG) and Alogliptin (ALG) in pure and bulk forms by simple, reproducible and highly sensitive spectrophotometric assays with detection at 530 (method A) and 520 nm (method B). The methods developed are based on the bleaching of above drugs with known excess of bromine. The unreacted bromine is determined based on its ability to bleach the dye Eriochrome blue black R (method A) and methyl red (method B) quantitatively at 530 (method A) and 520 nm (method B) for both the drugs obeying Beer's law in the range, 0.0-10.0 and 0.0-8.0 μg ml -1 in both the methods A and B for LNG and ALG, respectively. The values of molar absorptivity were found to be 1.53 × 10 4 and 2.51 × 10 4 l mol -1 cm -1 in method A and 1.64 × 10 4 and 2.82 × 10 4 l mol -1 cm -1 in method B, respectively with the corresponding Sandell's sensitivity values 0.0217 and 0.0188 μg cm -2 in method A and 0.0207 and 0.0167 μg cm -2 in method B. According to the current ICH guidelines, various validation parameters of proposed techniques were confirmed by applying the standard addition technique and the results were evaluated in terms of Student's t-test and variance ratio F-test to find out the significance of proposed methods over the earlier reported methods.